2023
DOI: 10.1186/s12890-023-02312-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors for incidence risk and prognosis of synchronous brain metastases in pulmonary large cell carcinoma patients: a population-based study

Abstract: Background Patients with pulmonary large cell carcinoma (LCC) have a high incidence of synchronous brain metastases (SBM) and a poor prognosis. Our study was to evaluate the predictive and prognostic value of the clinical characteristics of pulmonary LCC patients with SBM at initial diagnosis by utilizing the Surveillance, Epidemiology, and End Results (SEER) database. Methods LCC patients, diagnosed from 2010 to 2019, were identified from the late… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…The occurrence of radionecrosis was not observed in any of the patients, indicating that SIB-WBRT is safe and reliable. And after further analysis, it was found that the number of brain metastases in patients before treatment might be an independent prognostic factor for iPFS (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of radionecrosis was not observed in any of the patients, indicating that SIB-WBRT is safe and reliable. And after further analysis, it was found that the number of brain metastases in patients before treatment might be an independent prognostic factor for iPFS (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…The targeted-first therapy and radiotherapy-first treatment sequences have not been shown to significantly differ in terms of patient survival outcomes. Recent studies have demonstrated that there is no significant difference in patient survival between the targeted-first therapy and radiotherapy-first treatment sequences in patients with EGFR mutation-positive lung cancer brain metastases [16][17][18]. A clinical study conducted by Ke et al in 2018 observed 10 patients in the targeted therapy alone group who received targeted therapy first and then received radiotherapy as salvage therapy for failed metastasis control, and 10 patients in the radiotherapy alone group who received radiotherapy first.…”
Section: Discussionmentioning
confidence: 99%